2020
DOI: 10.3390/su12177048
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Feed-Forward Phase Locked Loop for Grid Synchronization of Renewable Energy Systems under Wide Frequency Deviations

Abstract: Synchronization is a crucial problem in the grid-connected inverter’s control and operation. A phase-locked loop (PLL) is a typical grid synchronization strategy, which ought to have a high resistance to power system uncertainties since its sensitivity influences the generated reference signal. The traditional PLL catches the phase and frequency of the input signal via the feedback loop filter (LF). In general, to enhance the steady-state capability during distorted grid conditions generally, a filter tuned fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Table 7 shows that the average load demand is 44, and the peak demand is 90.92 kW for the daily load profile. Consequently, the load factor is increased by about 1.5%, taking into account the daily load profile and by 3.8% for the monthly load profile [57][58][59][60][61]. It is confirmed that increasing the load factor enhances the energy efficiency measures on campus.…”
Section: Lf =mentioning
confidence: 64%
“…Table 7 shows that the average load demand is 44, and the peak demand is 90.92 kW for the daily load profile. Consequently, the load factor is increased by about 1.5%, taking into account the daily load profile and by 3.8% for the monthly load profile [57][58][59][60][61]. It is confirmed that increasing the load factor enhances the energy efficiency measures on campus.…”
Section: Lf =mentioning
confidence: 64%
“…Phase-Locked Loop (PLL) is used among various synchronization techniques to synchronize the SV to MHP in this study. PLL is a well-known, and widely used control technique for three-phase power systems is synchronous reference frame Phase Locked Loop (PLL) [26]. The modelling of SV is based on the mathematical equations where equations for voltage signal and power are shown below:…”
Section: Modelling Of Synchronvertermentioning
confidence: 99%
“…The power generated from RESs must be shaped in order to be interfaced with the grid by employing Power Electronics Converters (PEC) [3]. In grid-connected RES systems, the most popular synchronization technique is based on Phase-Locked Loops, (PLL) which synchronize the output power from the PEC with the electrical grid [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The second and third parts of SRF-PLLs are the Loop Filter (LF) and the Voltage-Controlled Oscillator (VCO) [8]. The LF is a Proportional Integrator (PI) controller that is mainly responsible for suppressing disturbances inside the PLL control loop.…”
Section: Introductionmentioning
confidence: 99%